The Influence of Organizational Culture on Organizational Citizenship Behavior with Employee Engagement as a Mediation Variable in Nurses at Tk. IV Singaraja Hospital - Yohannes Babtista Manik; A. Rohendi; Mira Veranita (CV. Civiliza Publishing, 2026)
The organizational management of nursing human resources in hospitals plays an important role in ensuring mutual service and patient safety. OCB behavior has benefits for the hospital, for example, nurses voluntarily participate in activities that benefit the company or do not complain during work. Organizational culture also influences employee psychological dimensions such as work motivation, job satisfaction, and organizational commitment. This study aims to analyze the influence of organizational culture on Organizational Citizenship Behavior with Employee Engagement as a mediating variable in nurses at Singaraja Level IV Hospital. The sample of this study consisted of 30 nurses working at the hospital. The analytical method used is descriptive analysis and hypothesis testing to clarify the relationship between organizational culture variables, organizational citizenship behavior and employee engagement. The results of the study indicate that organizational culture has a significant influence on nurses' OCB. In addition, organizational culture has also been shown to have a positive effect on employee engagement. These findings confirm that an effective organizational culture can increase OCB in nurses, which in turn will increase their employee engagement. The implication of this study is that hospital management needs to instill organizational culture in all nurses and optimize their performance and OCB in providing quality healthcare services.